Does Subsistence Farming Ameliorate Hunger in Urban Areas? A Quantitative Examination of Urban Areas in South Africa - Jonah, Coretta M.P.; Mabhena, Rejoice; May, Julian D. (Journal of Reviews on Global Economics, 2020)
Africa, with its growing urban population, faces the problem of increased demand for food in urban areas and pressure on urban food systems. Lack of employment opportunities, rising levels of urban poverty and food costs further compounds the urban food problem resulting in high levels of urban hunger and consequently food insecurity. Using the General Household Surveys from 2015 to 2017, we examine the association between subsistence farming practices and hunger in urban South Africa. We estimate three models for hunger at the household level; child hunger, adult hunger and hunger in either adult or child. The findings reveal that female-headed households are more likely to engage in subsistence farming. Women, children and the unemployed are at risk of hunger. We find no association between subsistence farming and hunger in urban areas. Measures of economic welfare; incomes, employment and a household member receiving a social grant are significantly associated with the absence of hunger. The results point to the fact that new urban residents as a matter of necessity need the means to earn an income as this is critical in safeguarding them from hunger.